Expression levels of insulin receptor substrate-1 modulate the osteoblastic differentiation of mesenchymal stem cells and osteosarcoma cells. (February 2014) - Contaldo, Clara; Myers, Timothy J.; Zucchini, Cinzia; Manara, Maria Cristina; Chiodoni, Claudia; Colombo, Mario P.; Nicoletti, Giordano; Lollini, Pier Luigi; Li, Tieshi; Longobardi, Lara; Scotlandi, Katia; Spagnoli, Anna
Abstract The insulin-like growth factor-1 system, including its critical mediator insulin receptor substrate-1 (IRS-1), is involved in regulating osteosarcoma (OS) cell proliferation or differentiation. The aim of this study is to define the role of IRS-1 in OS cells by assessing the contribution of IRS-1 in the differentiation of human and murine OS cell lines and mouse mesenchymal stem cells (MSCs) and found that the basal level of IRS-1 is important for the initiation of differentiation. Both down-regulation and over-expression of IRS-1 inhibited osteoblastic differentiation. In vivo studies showed that OS cells over-expressing IRS-1 have increased metastatic potential and tumor growth. The proteasome inhibitor MG-132 led to an increase in IRS-1 protein level that inhibited osteoblastic differentiation, suggesting a role for proteasomal regulation in maintaining the appropriate expression level of IRS-1. Thus, precise regulation of IRS-1 expression level is critical for determining the differentiating capacity of MSCs and OS cells, and that derangement of IRS-1 levels can be a critical step in OS transformation.